2015
DOI: 10.1080/00380768.2015.1106923
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for bright-field imaging of arbuscular mycorrhizal fungi in plant roots

Abstract: Easy observation methods to assess the colonization levels of arbuscular mycorrhizal (AM) fungi in plant roots are crucial for studying the biology of AM symbiosis and for considering agricultural use. Many AM studies employ Trypan Blue (TB) coupled with lactic acid to stain AM fungal structures as bright-field images; however, TB staining can be difficult to use owing to its noxiousness and high viscosity. Here, we report the development of an easy method for visualizing AM fungal structures as bright-field i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…The roots were stored at −80 • C to estimate colonization by AMF and DNA extraction. The fresh roots were stained with a 3,3 -diaminobenzidine (DAB) solution [41]. The colonization by AMF in the tomato plants was estimated according to the method of Giovannetti and Mosse [42].…”
Section: Root Sampling and Stainingmentioning
confidence: 99%
“…The roots were stored at −80 • C to estimate colonization by AMF and DNA extraction. The fresh roots were stained with a 3,3 -diaminobenzidine (DAB) solution [41]. The colonization by AMF in the tomato plants was estimated according to the method of Giovannetti and Mosse [42].…”
Section: Root Sampling and Stainingmentioning
confidence: 99%
“…We previously established a WGA-HRP-DAB staining method for the bright-field imaging of AM fungal mycelia in roots of diverse plant species (Kobae and Ohtomo 2016). This staining method is high contrast and low background, and allows the recognition of symbiotic structures of AM fungi under low microscopic magnification.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in general, these methods require the preparation of specimens and observation under high magnification (McGonigle et al 1990). We previously reported that the application of WGA-conjugated horseradish peroxidase (HRP) with 3,3ʹ-diaminobenzidine (DAB) (WGA-HRP-DAB staining) successfully excludes the background signals of cortex and steles (Kobae and Ohtomo 2016). This method enables the identification of AM fungal structures in roots with extremely high contrast and simple bright-field imaging that can be performed with bright-field stereomicroscopy at only 15× magnification (Kobae and Ohtomo 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kobae and Ohtomo (2016) established a WGA (wheat germ agglutinin)-HRP (horseradish peroxidase)-DAB (3,3ʹ-diaminobenzidine) staining method for the bright-field imaging of AM fungal mycelia within roots of soybean and other plant species. In this method, WGA-conjugated HRP, which specifically targets N-acetylglucosamine polymers and detects AM fungal cell walls, penetrated the cortical layers of 10% potassium hydroxide-treated host roots and stained AM fungal mycelia in the presence of DAB and hydrogen peroxide.…”
Section: Mycorrhizal Intensity (%)mentioning
confidence: 99%